Rhodamine-modified upconversion nanophosphors for ratiometric detection of hypochlorous acid in aqueous solution and living cells - Zhou, Yi (2014)
Hypochlorous acid (HOCl), a reactive oxygen species (ROS) produced by myeloperoxidase (MPO) enzyme-mediated peroxidation of chloride ions, acts as a key microbicidal agent in immune systems. However, misregulated production of HOCl could damage host tissues and cause many inflammation-related diseases. Due to its biological importance, many efforts have been focused on developing fluorescent probes to image HOCl in living system. Compared with those conventional fluorescent probes, up-conversion luminescence (UCL) detection system has been proven to exhibit a lot of advantages including no photo-bleaching, higher light penetration depth, no autofluorescence and less damage to biosamples. Herein, we report a novel water-soluble organic-nano detection system based on rhodamine-modified UCNPs for UCL-sensing HOCl. Upon the interaction with HOCl, the green UCL emission intensity in the detection system were gradually decreased, but the emissions in the NIR region almost have no change, which is very important for the ratiometric UCL detection of HOCl in aqueous solution. More importantly, RBH1-UCNPs could be used for the ratiometric UCL visualization of HOCl released by MPO-mediated peroxidation of chloride ions in living cells. This organic-nano system could be further developed into a novel next-generation imaging technique for bio-imaging HOCl in living system without background noise.